Heterogeneous impacts of mobility restrictions on air quality in the State of Sao Paulo during the COVID-19 pandemic. (1st May 2022) - Cirqueira, Samirys Sara Rodrigues; Rodrigues, Patricia Ferrini; Branco, Pedro; Vormittag, Evangelina; Nunes, Rafael; Anastacio, Andressa Vilas Boas; Veras, Mariana; Sousa, Sofia; Saldiva, Paulo Hilário Nascimento
Abstract: Air quality in the State of Sao Paulo was evaluated during the first general State plan of mobility restrictions due to the COVID-19 pandemic (24th March to May 31, 2020). Nitrogen dioxide (NO2 ), ozone (O3 ), particulate matter PM10 and PM2.5 and sulphur dioxide (SO2 ) concentrations were assessed in cities of the Sao Paulo State with a monitoring station and compared to historical data. Linear regression models were built to investigate the relationship between the isolation of the population – determined using mobile phone monitoring data - and the concentration of each pollutant during the studied period. Although the reduction of pollutants such as NO2, SO2 and PM2.5 is very clear, the economic and climatic characteristics of each region were decisive in the general behaviour of O3 and PM10 . It was not possible to establish a correlation between the pollutants and the isolation index, partly due to the lack of data, partly due to the compliance of the population to those measurements, which was variable over time. Another important limitation factor was the absence of data related to the pollutants of interest in many of the stations. However, the isolation measures carried out in the State opened the opportunity to individually assess the air quality measurements in each of the stations, enabling an understanding that will allow in the future the design of air quality policies together with local sanitary policies. Graphical abstract: Image 1 Highlights: We assessed the impact of mobility restrictions on air pollution in Sao Paulo. 65 stations where used to assess air quality in 35 cities. NO2, O3, PM2.5, PM10 and SO2 in 2020 were compared to historical data. Results show heterogeneous changes in air quality and no correlation with mobility. Air quality policies should consider health and economic regional differences.